Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = \dfrac{3x - 2}{5}}[/tex]
[tex]\mathsf{y = \dfrac{3x - 2}{5}}[/tex]
[tex]\mathsf{x = \dfrac{3y - 2}{5}}[/tex]
[tex]\mathsf{5x = 3y - 2}[/tex]
[tex]\mathsf{3y = 5x + 2}[/tex]
[tex]\mathsf{y = \dfrac{5x + 2}{3}}[/tex]
[tex]\boxed{\boxed{\mathsf{f^{-1}(x)= \dfrac{5x + 2}{3}}}}[/tex]
Explicação passo-a-passo:
[tex]f(x) = \frac{3x - 2}{5} [/tex]
[tex]y = \frac{3x - 2}{5} [/tex]
[tex]x = \frac{3y - 2}{5} [/tex]
[tex]5x = 3y - 2[/tex]
[tex]x = \frac{3y - 2}{5} [/tex]
[tex]3y = 5x + 2[/tex]
[tex]y = \frac{5x + 2}{3} [/tex]
f-¹(x)= (5x+2)/3